Development Of Physical Fitness Teaching Materials E-Book Using Flipbook Maker - Khurotul Aini; Aisya Kemala (STKIP Muhammadiyah Kuningan, 2022)
Physical fitness is essential in maintaining body condition during a pandemic. In physical education learning, delivering exciting and media-based technology material increases students' interest in learning activities. This research aims to develop physical fitness teaching materials based on flipbook maker media for junior high school age. The design of this research refers to the 4D development model, namely, the analysis is carried out through four stages: (1) Define, (2) Design, (3) Development, and (4) Disseminate. This research resulted in a flipbook-based physical fitness teaching material product that had been evaluated by three experts and was declared worthy of a trial. This study uses a total of 30 students. The data analysis technique used in this study used quantitative descriptive statistics with the effectiveness test using the t-test. The study results resulted in an e-book product of physical fitness teaching materials using traditional flipbook maker-based games that have been tested and validated by experts with appropriate categories and can increase students' physical fitness levels and develop students' talents and interests in participating in physical education learning activities. So it can be concluded that physical fitness teaching materials through traditional games based on flipbook maker media can improve the physical fitness of junior high school-age students.